TRANSLATION AND STRATEGIES (Лучшие интеллектуальные исследования, 2025)
Abstract: Translation is the process of transferring meaning from one language to another. It is essential for global communication, literature, science, and education. This paper introduces translation as a field of study, explores its main types, discusses common strategies used by translators, and highlights the differences between English and Uzbek translation practices.